This study sought to determine the impact of spreading the culture of quality in improving the quality of tourism service in some hotels in Erbil governorate - احمد احمد طلال; علي بسام منيب (Journal of Economics and Administrative Sciences, 2019)
This study sought to determine the impact of spreading the culture of quality in improving the quality of tourism service in some hotels in Erbil governorate. The theme of excellence in providing service and attention to it has become the concern of most organizations in general and tourism service organizations in particular. Tourists try to establish the mental status of customers about their tourism organizations had to pay attention to the quality of service provided to the customer and work to develop them to the advanced stages of satisfaction and happiness of customers and this will certainly positively affect the improvement of service in the tourism sector, Of the research variables were examined statistically by distributing the questionnaire to the employees of these hotels and their customers, and then analyzing the data and reaching conclusions and proposals that serve this segment of organizations.